Determining the Concept of the Principles of Legal Regulation of Encouragement of the Employees of the National Police of Ukraine - N. V. Sorochan (Bulletin of Kharkiv National University of Internal Affairs)
The author has researched one of the directions of the modern formation and development of the rule of law state related to the improvement of various branches of law and the relevant legislation in the field of labor law, the definition of the concept and principles of legal regulation of encouragement applicable to the employees of the National Police of Ukraine.